Balance, General Cognition and Lower Motoric Strength in Elderly: Tai Chi Versus Brisk Walking - Steven Kelvin Anam; Marina A. Moelino; Yuni S. Pratiwi (Althea Medical Journal, 2017)
Background: The number of elderly in Indonesia continues to increase. A better quality of life can be achieved by preventing reduction of elderly’s cognition, balance and strength of the lower extremities. Tai Chi has been suggested as one of the sports to maintain cognition, balance and lower extremity strength for elder people. However, there are still few studies that compare Tai Chi to other exercises. The aim of this study was to compare the effects of practicing Tai Chi verrsus brisk walking.Methods: The study design was observational, cross-sectional. Elderly who practiced Tai Chi and Brisk-walk in Tegalega sport field were chosen as the target population. The respondents must be at least 60 years old, no history of cardiovascular disease in the last 3 months, no musculoskeletal complaints, no obvious signs and symptoms of chronic diseases. Afterwards, the respondents were examined using Timed Up and Go (TUG) Test for balance, Montreal Cognitive Assessment (MoCA) for cognition and leg dynamometer for the lower extrimities strength. The collected data was analyzed using Mann-Whitney statistical test and Kolmogorov-Smirnov test.Results: No significant difference was detected among the three parameters between Tai Chi group (TCG) and Brisk Walking group (BWG). Difference of 0.5 (p=0.314) and 0.6 (p=0.554) was found for TUG Test and MoCA Test between TCG and BWG using Mann Whitney. The leg dynamometer was tested using Kolmogorov-smirnov (p = 1.00).Conclusions: Similar result of balance, cognition, and lower motor strength are found between TCG and BWG.  DOI: 10.15850/amj.v4n2.1063